Short-wave infrared organic phototransistors with strong infrared-absorbing polytriarylamine by electron-transfer doping - Chulyeon Lee (Nature Portfolio, 2021)
Abstract Short-wavelength infrared (SWIR) sensors have attracted keen attention due to the increasing necessity in a variety of scientific and industrial applications, including biomedical and information technology fields. Because conventional SWIR sensors are made of inorganic materials with rigid and brittle characteristics, organic materials with a discrete SWIR absorption are required for flexible SWIR sensors in the flexible electronics era. Here, we demonstrate that a polytriarylamine, poly[N,N′-bis(4-butylphenyl)-N,N′-bis(phenyl)benzidine] (PolyTPD), can absorb almost full range of SWIR wavelength (λ = 1000–3200 nm) after 48 h doping with tris(pentafluorophenyl)borane (BCF). The spectroscopic characterization disclosed that an electron transfer from PolyTPD to BCF created a new low energy level (gap) state leading to the SWIR absorption in the BCF-doped PolyTPD complexes. Organic phototransistors (OPTRs) with the BCF-doped PolyTPD films as a gate-sensing layer could detect the SWIR light with a reasonable photoresponsivity of ~538 mA W−1 (λ = 1500 nm), ~541 mA W−1 (λ = 2000 nm), and ~222 mA W−1 (λ = 3000 nm). The present breakthrough SWIR-OPTR technology can pave a way for further advances in SWIR-absorbing organic materials and flexible SWIR sensors.